VCP maintains nuclear size by regulating the DNA damage-associated MDC1–p53–autophagy axis in Drosophila - Ya-Chu Chang (Nature Portfolio, 2021)
Cells maintain a constant cytoplasm to nucleus volume ratio, although the role of DNA damage is not well explored. Here, the authors use Drosophila to connect TER94, the fly homolog of VCP, to disruption of DNA damage repair, leading to ubiquitinated Mu2 protein accumulation and enlarged nuclei.